Adolescent Reproductive Health Care: Views and Practices of Pediatric Hospitalists - Masonbrink, Abbey R. (Hosp Pediatr, 2019)
BACKGROUND AND OBJECTIVES: Many hospitalized adolescents are at increased risk for pregnancy complications due to an underlying medical condition, however sexual risk assessment is not consistently performed in this setting. While adolescents and their parents are supportive of sexual health discussion in the inpatient setting, a thorough understanding of factors that influence provision of this care among pediatric hospital physicians is lacking. This formative information is needed to facilitate efforts to improve and standardize clinical care provision. Our objective is to assess the frequency and factors that influence the provision of adolescent sexual and reproductive care by pediatric hospitalists. METHODS: We performed a cross-sectional computerized survey of hospitalists at 5 pediatric hospitals who cared for ≥1 adolescent (14–21 years old) in the past year. Sexual and reproductive care practices were assessed by using a 76-item novel survey informed by the theory of planned behavior. We used descriptive statistics to summarize the data. RESULTS: Sixty-eight pediatric hospitalists participated (49% response rate): 78% were women and 65% were aged <40 years. Most (69%) reported treating >46 adolescents annually, including many who are at an increased risk for pregnancy complications due to teratogenic medication use or a comorbid condition. A majority felt that sexual and reproductive services are appropriate, although many endorsed barriers, including concern about follow-up after emergency contraception (63%) and time constraints (53%). Most reported insufficient knowledge regarding contraception (59%), desired contraception education (57%), and were likely to increase contraceptive provision if provided education (63%). Hospitalists rarely provided condoms or referral for an intrauterine device. CONCLUSIONS: Pediatric hospitalists frequently care for adolescents who are at risk for pregnancy complications and generally agree that reproductive care is appropriate in the inpatient setting. With these findings, we highlight the critical need for effective comprehensive reproductive health service interventions that are tailored to address the numerous actionable barriers identified in this study.